Can Urbanization Influence Carbon Dioxide Emissions? Evidence from BRICS–T Countries - Somoye, Oluwatoyin; Akinwande, Toluwalope Seyi (Journal of Contemporary Urban Affairs, 2023)
Climate change is one of several issues confronting the planet today. Addressing this problem will create a safer environment for humans and other species. Thus, this study explores how the urban population (UBNP) influences carbon dioxide emissions (CO2e) levels in BRICS–T from 1990–2021 (192 observations) using Pooled OLS and Fixed Effects techniques. In addition, energy intensity (ENIT) and economic growth (GDP) are utilized as control variables. The Pooled OLS result demonstrates that UBNP growth reduces CO2e by 0.19%; a rise in ENIT levels spurs CO2e by 1.10%, and an increase in GDP enhances CO2e by 0.61%. The Fixed Effects outcome shows that an upsurge in UBNP reduces CO2e by 1.19%, while ENIT and GDP rise boosts CO2e by 1.19% and 1.04%, respectively. This study recommends continuous urban planning, rural area development, renewable energy integration, and the use ofenergy–efficient buildings.